PENINGKATKAN MOTIVASI BELAJAR PPKn MELALUI MEDIA PEMBELAJARAN LCD PROJECTOR PADA SISWA KELAS VII.4 SMPN 1 LUHAK NAN DUO - Azibah, Azibah (TINGKAP, 2016)
ABSTRACTÂ This action research aims to determine whether LCD Projector learning medium can improve students' learning motivation in Civics class of VII.4 SMP Negeri 1 Luhak Nan Duo. This study was conducted with a qualitative approach through Classroom Action Research. The study was conducted in two cycles. Data of teachers and students activities obtained from the observer by using observation sheets. The findings show that civics learning using LCD Projector medium can improve students' learning motivation in Civics class of VII.4 SMPN 1 Luhak Nan Duo. In addition, 25 of the 34 students who take daily tests have reached the minimum mastery criteria (KKM). Based on the results of this study, it is concluded that learning activities using LCD Projector medium can improve students' learning motivation in Civics class of VII.4 SMPN 1 Luhak Nan Duo.Key Words: Student learning motivation, LCD projector, learning medium, Citizenship Education